Castleman disease. A rare diagnosis in childhood - Cunha,Sara Monteiro (2021)
Abstract Introduction: Castleman Disease (CD) is a rare polyclonal lymphoproliferative disorder characterized by massive growth of lymphoid tissue. The most common sites of disease are the chest, abdomen, neck, and axilla. Excisional biopsy is mandatory for diagnosis, and complete surgical resection the gold-standard treatment in unicentric CD. Case report: A ten-year-old girl was observed at the Emergency Department with sore throat and fever. Oropharynx examination revealed inflamed tonsils, with no exudates. Enlarged lymphadenopathy was palpable in the right supraclavicular fossa. Ultrasound revealed right supraclavicular lymphadenopathy with loss of adipose hilum and histopathologic assessment established CD diagnosis. Discussion/Conclusion: Lymphadenopathy is a common presentation in children, usually benign and self-limited. But it may also be a sign of underlying malignancy. Any lymphadenopathy in the supraclavicular fossa is worrisome and requires prompt investigation. CD diagnosis may be challenging, due its rare nature in childhood and nonspecific symptoms.